Amazing Animals / Animales Increibles (New York : Childrens Press, 2017)
Photographs labeled in English and Spanish introduce young readers to the words for common animals that are divided into nine different categories, including big eyes, long legs, and hard shells.
"18 months and up"--Back cover.
Board book in Spanish and English.
Keywords: Animales; Literatura juvenil; Spanish language -- Vocabulary; Juvenile literature; Animals -- Juvenile literature; Spanish language; Bilingual books; Picture books; Literature